2021
DOI: 10.47108/jidhealth.vol4.iss2.106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the home isolation of COVID-19 patients in primary care

Abstract: Background: This study aims to evaluate the effectiveness of home isolation and medical follow-up by analyzing data collected over the phone from isolated individuals. Methods: A cross-sectional phone-based survey designed to evaluate the home isolated COVID-19 suspected patients at the Şişli Hamidiye Etfal Family Health Center in Istanbul city between 16th  March  5th May 2020.  A semi-structured questionnaire and the universal sampling technique were recruited to collect data about the socio-demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Many factors are discussed to understand the motives that may contribute to the decision-making process regarding the acceptance or rejection of the vaccine among HCPs. Previous studies [3,[7][8][9][10] have acknowledged the distinct role of health professionals in addressing the COVID-19 pandemic, which made them the most vulnerable professions to infection with the virus. No doubt they have the priority in receiving the vaccine because they are the front line of defense when responding to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors are discussed to understand the motives that may contribute to the decision-making process regarding the acceptance or rejection of the vaccine among HCPs. Previous studies [3,[7][8][9][10] have acknowledged the distinct role of health professionals in addressing the COVID-19 pandemic, which made them the most vulnerable professions to infection with the virus. No doubt they have the priority in receiving the vaccine because they are the front line of defense when responding to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high absenteeism rates were recorded among health care providers (HCPs) for many reasons, such as exposure to COVID-19 infection and isolation as a Precaution to prevent the spread of infection [4,5]. Since the declaration of coronavirus as a global pandemic on 11th March 2020, hundreds of thousands of patients have had an influx of health care facilities in large parts of the world simultaneously, causing enormous pressure on healthcare facilities and HCPs, respectively [6,7,8]. There is no doubt that healthcare providers constitute the highest priority group for coronavirus vaccination [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 27 ] In a study from Istanbul in Turkey, it was found that only 56.2% of COVID-19 patients used masks in common areas during isolation and 21.2% even left their homes during isolation at least once. [ 28 ] In a mathematical model by Borame L Dickens comparing the effectiveness of home isolation to that of institutional isolation in curtailing cases during an outbreak, it was found that the strategy of home-based isolation could result in an 8-day delay in the epidemic peak, whereas Institution-based isolation could create a peak delay of 18 days. [ 29 ] Thus, failure of compliance of strict room isolation could be one of the major factors that could have triggered the huge surge in cases during the second wave.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the accelerating number of patients, the number of beds available in the hospital became limited, so as a result, home isolation programs were established. In October 2021, the home isolation program was launched, which is similar to the policy invoked in many countries for example Turkey [ 4 ], Germany [ 5 ], and India [ 6 ]. This service allows people with COVID-19 to receive treatment at home and be monitored by the incorporation of telemedicine into the care system.…”
Section: Introductionmentioning
confidence: 99%